2020
DOI: 10.1097/pr9.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

The early influence of COVID-19 pandemic-associated restrictions on pain, mood, and everyday life of patients with painful polyneuropathy

Abstract: Supplemental Digital Content is Available in the Text. Validated questionnaires revealed a shift of attention from chronic pain towards the COVID-19 pandemic in patients with chronic painful polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Interestingly, in a study investigating 43 chronic German pain patients within the first 2 weeks after the initial lockdown (ie, including, among other restrictions, prohibitions of private gatherings of any kind, closures of recreational and day-care facilities as well as schools, closures of shops not urgently needed for daily life, cancellations of all planned admissions to hospitals that were not emergency-related, strict regulations for the visitation of patients in hospitals or nursing homes, cancellations of public events, and travel restrictions), pain intensity remained stable or even improved. 41 In this time period, only 11.6% of the entire cohort reported a pandemic-associated worsening of pain, whereas 48.8% reported a worsening of mood. Rumination scores of the pain catastrophizing scale also decreased during that time.…”
Section: Impact Of the Covid-19 Pandemic On Chronic Pain Patientsmentioning
confidence: 77%
See 2 more Smart Citations
“…Interestingly, in a study investigating 43 chronic German pain patients within the first 2 weeks after the initial lockdown (ie, including, among other restrictions, prohibitions of private gatherings of any kind, closures of recreational and day-care facilities as well as schools, closures of shops not urgently needed for daily life, cancellations of all planned admissions to hospitals that were not emergency-related, strict regulations for the visitation of patients in hospitals or nursing homes, cancellations of public events, and travel restrictions), pain intensity remained stable or even improved. 41 In this time period, only 11.6% of the entire cohort reported a pandemic-associated worsening of pain, whereas 48.8% reported a worsening of mood. Rumination scores of the pain catastrophizing scale also decreased during that time.…”
Section: Impact Of the Covid-19 Pandemic On Chronic Pain Patientsmentioning
confidence: 77%
“…Further analysis revealed that patients who had experienced a change in social life as a consequence of pandemic restrictions had higher pain ratings than those without, and feelings of helplessness increased in those patients with higher pain ratings. 41 The results therefore suggest a shift of attention from the chronic pain condition towards the imminent threat of a global pandemic at the beginning of the lockdown. 41 In view of the often postulated stages that are passed through in the course of pandemics, 20 it seems plausible that patients were still in the so-called “heroic” or “honeymoon” phase at the time of the survey.…”
Section: Impact Of the Covid-19 Pandemic On Chronic Pain Patientsmentioning
confidence: 88%
See 1 more Smart Citation
“…This is also the second quantitative study investigating the psychological functioning of in people with chronic pain in the pandemic. One quantitative study investigated early influence of the pandemic in Germany, 26 where patients with painful polyneuropathy were assessed two weeks after COVID-related regulations came into effect, while current study collected data from people with chronic pain in the community, about three to four months into the pandemic. In one mixed methods study in people with chronic pain, 34 correlations between measures of mental health collected (several weeks to several years) prior to the pandemic, and one PF process (pain acceptance) measured during the pandemic, were reported.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, people with chronic pain and anxiety disorder experience greater pain, worse psychological outcomes, and lower quality of life, compared to those without, and severity of anxiety disorder is strongly associated with the level of functional impairment in these people. 29 In one study of early influence of the pandemic on people with painful polyneuropathy, 26 more than half of the participants reported being more worried about their health than before the pandemic. In addition, about half of the participants experienced medical disadvantages and/or worsened mood due to the pandemic, and 28% reported worsened sleep due to the pandemic.…”
Section: Introductionmentioning
confidence: 99%